Understanding the role of arrangement of treasury archives in preventing fraud at regional financial and revenue management agency - Rasmadi; Maryadi; Sjarlis , Sylvia (Publication Division of International Ecsis Association, 2022)
This research aims to test the influence of the implementation of disbursement information systems, the arrangement of treasury archives, and leadership support for fraud prevention in the financial and revenue management agency of West Sulawesi province. This research approach uses a descriptive quantitative approach. The population of this study is the head of subsection and head of the financial subfield and treasurer of each the financial and revenue management agency of West Sulawesi province. The sampling techniques in this study was used purposive sampling. The results of this study showed that variable disbursement of funds, arrangement of archives and leadership support had a significant impact in the prevention of fraud in the Financial and Regional Revenue Management Agency of West Sulawesi Province both partially and simultaneously. The archive structuring variables had the most dominant influence among all independent variables on dependent variables in this study. This study has the implications that good and archive structuring will prevent fraud in the West Sulawesi Provincial Financial and Revenue Management Agency.